Evaluating Dancers' Participation Motives: The Use of the Greek Version of the BRSQ - Filippou Filippos; Tsitskari Efi; Bebetsos Evangelos; Goulimaris Dimitris (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
The study's aim was to cross-validate the "Behavioral Regulation in Sport Questionnaire" (BRSQ), of Lonsdale and his co-authors (2008) in a Greek dance context. The sample consisted of 390 dancers, 249 coming from folk dance groups and 141 from non-folkdance groups. The scale was translated into Greek using the back-translation procedure. The validity and reliability of the questionnaire were checked by performing a confirmatory factor analysis (CFA) and an internal consistency analysis using Cronbach's alpha. Descriptive statistics were calculated to broadly examine the participation motives and Independent samples t-test calculated the differences in the participants' motives according to the kind of dance they chose to participate in. The Greek version of BRSQ showed stable psychometric properties. Intrinsic motivation is highly evaluated by both traditional and modern/classic dance participants, though the participants of different types of dances statistically different evaluate some of their intrinsic and extrinsic motives of participation.